Unveiling the Psychology of Human-Computer Interaction: Bridging the Gap for Future Advancements - Baharum A.; Rahim E.A.; Ismail R.; Noor N.A.M.; Daruis D.D.I.; Deris F.D.; Samat J. (Institute of Electrical and Electronics Engineers Inc., 2024)
This paper brings some light to the importance of psychology as a concept, its initial role in human-computer interaction, and exactly how necessary it is to maintain this aspect when spearheading the future of the field. The method used is to decipher what psychology gives to Human-Computer Interaction (HCI), including the primary components, the task, user, and computer. The results of this study discuss the framework of previous research, and how it stands today considering modern sub-theories. In the end, the verdict stands that psychology as one of the feature of HCI applies primarily to authors in the United States, and very much less when it comes to European researchers, who would generally take different approaches to their research. It is necessary to have a consistent conversation on the gravity of connecting the researchers of HCI and advancements with the full extent and realm of studies that exist. One of the biggest things that this paper brings to the field is some focus on the necessity that there is for in-depth analysis of psychology as a method of approaching HCI. 2023 IEEE.